Multilingualism and gender in the UAE: A look at the motivational selves of Emirati teenagers. (August 2019) - Calafato, Raees; Tang, Fei
Abstract: This study examines the motivational self concepts of seventy-three Emirati Arab adolescents from the United Arab Emirates who are studying in English-medium schools and learning an additional foreign language (L3). Using the L2 Motivational Self System framework, this study specifically explores gender differences in participants' ideal and ought-to motivational selves, as well as their desire to be multilingual, while also taking years of study and language ability into account. The results of the study indicate that while male and female participants' ideal L3 self concepts differ significantly in terms of motivational intensity, their ought-to L3 selves differ to a much lesser extent. Female participants also appear to be more motivated to be multilingual. Gender differences are mostly absent with respect to participants' English self concepts and both genders appear to be more extrinsically motivated to learn the language. The findings also indicate that participants' English self concepts do not, in general, significantly correlate with their L3 self concepts. This study not only adds to the growing body of research on language learning motivation within the framework of multiple future self concepts, but also sheds light on multilingual motivation in the Gulf context as it concerns school-going adolescents.